(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2017)
This fragment illustrating the diagram on various traffic control models, overview of control and management functions and emission control relationship with isolated and coordinated intersections. Related works on emission control etc. are presented. This paper presenting the survey on various controlling concepts for urban and suburban roads by presenting the literature survey on two points such as first is relationship between emission control and isolated intersection, and second is relationship between coordinate intersection and emission control. This paper presents the review of various vehicle emission estimation models and also related works on study on relationship between emission control and traffic control.